Disadvantages in Differentiation and Exceeding Limits of Necessary Defense According to the Legislation of the Republic of Kazakhstan - BAZILOVA, Aigul Abaevna (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
The article shows that the specificity and content of criminal law due to the tasks that lie before him. It is shown that a criminal law tasks the author defines the protection of rights, freedoms and legitimate interests of man and citizen, property, rights and legitimate interests of organizations, public order and safety, environment, constitutional order and territorial integrity of the Republic of Kazakhstan, the legally protected interests of society and the state from criminal attacks, protecting the peace and security of mankind, as well as the prevention of crime, to which belong and the necessary self-defense. For the foundation of criminal responsibility in article defines what hazardous to individuals, society or the state acts are crimes, prescribes penalties and other measures of criminal law for their commitment, that is, these problems are solved in the process of implementation of the regulatory and enforcement functions of the criminal law.